Prediction of bandgaps in membrane-type metamaterial attached to a thin plate - Gao, Cong; Halim, Dunant; Rudd, Chris (Institute of Noise Control Engineering, 2019)
This work proposes an analytical method to analyse the bandgap location and width of membrane-type metamaterial when it is attached to a thin plate structure. This method enables the bandgap prediction of such a structure by adjusting the tensile stress of the membrane directly. The accuracy of the model is verified by constructing a finite structure model for numerical simulation and comparing the results. It shows that the results given by the analytical model are primarily consistent with the simulation. The effect of membrane tensile stress and attached mass on the bandgap location and width is also investigated. It is found that the width of bandgap can be increased by increasing the membrane tensile stress and using a heavier mass attached to the membrane.